Public Art: a Review. Social and Political Practices - Styliani Bolonaki (European Journal of Creative Practices in Cities and Landscapes)
Public art covers a range of phenomena in which aesthetics and urban life intersect. Public art introduces a broad of practices that opened to a number of interpretations regards their contributions to the urban environment, functions as a key factor in a city’s regeneration policies, and is the primary fuel of urban capital production and accumulation today. The article focuses on the art practices that declare ethical commitments with the social-political sphere, promoting participatory and collaboratively-led activities, converging thus with the dynamics of activist practices. The article reconsiders the role of public art as a socio-political agent, taking into account the timeless self-defining and self-regulating autonomy of visual arts, which claims the right to set specific norms of cultural inclusion and exclusion in the public space, reducing thus the multiculturalism of urban life to the restrictive framework of a one-dimensional culture. The paper elaborates on some aspects of the discussions about the social-political engagements of public art, developing a brief discussion of some of the most current themes emerging from it.